Geometric optimization of shells - BROI, P (Computer aided optimum design in engineering X, 2007)
The selection of forward-looking evolution philosophies for the dynamic optimization of slender shell structures subject to load impact is handled. The wave mechanics in identification outlook is applied to numerical analysis of the problem. Employing the force method of analysis and provisionally neglecting the implicit compatibility conditions, an approximate explicit problem is presented. After solving this problem a lower limit of the optimum is effectively obtained. To assess the real optimum of the implicit problem, the compatibility conditions are taken into account for the final geometry. Several approximation concepts are proposed for the effective solution of the explicit fixed geometry problem. Linear programming models and approximate treatment of the displacement constraints are presented. The proposed algorithms do not involve multiple implicit analyses of the construction.